PAMELA: A REFLECTION OF A NEW 18TH CENTURY WOMAN - Galuh Prameswari; Ekawati Marhaenny Dukut; B. Retang Wongahara (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
The 18'" century period is often considered as a period where women had to live ill men's world. There were norms, values, and rules, which binded, tied and controlled women's movements in every part of life. Women 'were forced' to be only as men 's servants and slaves who were obliged to be submissive and servile. Through his novel, Pamela, Samuel Richardson introduces his main character. Pamela. as a controversially different character. She changes the meaning of servitude, in which women do not have to be men's properties for being servile. Unlike most women ill her century. she introduces herself as a being who ;s able to use her intelligence in defending her rights in front of men ill a patriarchal society while at the same time she still gives her respect to them. This article, which uses traditionally, sociological. moral, and feminism approaches. is intended to analyze the new portrayal of the 18'" century female character by focusing on Samuel Richardson's Pamela, as she showed new meanings of being a woman, a wife. and a mother to her husband, friends and society.